Microstructural Evolution of 9CrMoW Weld Metal in a Multiple-Pass Weld - Yu-Lun Chuang; Chu-Chun Wang; Tai-Cheng Chen; Ren-Kae Shiue; Leu-Wen Tsay (Metals, 2021)
9CrMoW steel tubes were welded in multiple passes by gas-tungsten arc welding. The reheated microstructures in the Gr. 92 weld metal (WM) of a multiple-pass weld were simulated with an infrared heating system. Simulated specimens after tempering at 760 °C/2 h were subjected to constant load creep tests either at 630 °C/120 MPa or 660 °C/80 MPa. The simulated specimens were designated as the over-tempered (OT, below AC1, i.e., WT-820T) and partially transformed (PT, below AC3, i.e., WT-890T) samples. The transmission electron microscope (TEM) micrographs demonstrated that the tempered WM (WT) displayed coarse martensite packets with carbides along the lath and grain boundaries. Cellular subgrains and coarse carbides were observed in the WT-820T sample. A degraded lath morphology and numerous carbides in various dimensions were found in the WT-890T sample. The grain boundary map showed that the WT-820T sample had the same coarse-grained structure as the WT sample, but the WT-890T sample consisted of refined grains. The WT-890T samples with a fine-grained structure were more prone to creep fracture than the WT and WT-820T samples were. Intergranular cracking was more likely to occur at the corners of the crept samples, which suffered from high strain and stress concentration. As compared to the Gr. 91 steel or Gr. 91 WM, the Gr. 92 WM was more stable in maintaining its original microstructures under the same creep condition. Undegraded microstructures of the Gr. 92 WM strained at elevated temperatures were responsible for its higher resistance to creep failure during the practical service.